3-Aminopiperidine-Based Peptide Analogues as the First Selective Noncovalent Inhibitors of the Bacterial Cysteine Protease IdeS - Berggren, Kristina (American Chemical Society, 2012)
[Image: see text] A series of eight peptides corresponding to the amino acid sequence of the hinge region of IgG and 17 newly synthesized peptide analogues containing a piperidine moiety as a replacement of a glycine residue were tested as potential inhibitors of the bacterial IgG degrading enzyme of Streptococcus pyogenes, IdeS. None of the peptides showed any inhibitory activity of IdeS, but several piperidine-based analogues were identified as inhibitors. Two different analysis methods were used: an SDS-PAGE based assay to detect IgG cleavage products and a surface plasmon resonance spectroscopy based assay to quantify the degree of inhibition. To investigate the selectivity of the inhibitors for IdeS, all compounds were screened against two other related cysteine proteases (SpeB and papain). The selectivity results show that larger analogues that are active inhibitors of IdeS are even more potent as inhibitors of papain, whereas smaller analogues that are active inhibitors of IdeS inhibit neither SpeB nor papain. Two compounds were identified that exhibit high selectivity against IdeS and will be used for further studies.